Kemenangan Caleg Perempuan dari Partai Perindo di DPRD Kabupaten Asahan dalam Pemilu Legislatif 2019 - -, Wahyu; Noak, Piers Andreas; Apriani, Kadek Dwita (Jurnal Nawala Politika, 2022)
This research to describe the factors that can influence the victory of female candidates from the Perindo party in the Asahan Regency DPRD in the 2019 legislative elections. The community environment in Asahan which is still thick with patriarchal culture is one of the challenges that must be faced by female candidates. Factors that influence the victory of female candidates are the values possessed by female candidates and the closest male figures who support female candidates and have strengths that can be utilized. Therefore, the researcher used the concept of Male Power Relations to describe the winning factors for female candidates in Asahan. This research then found the answer that the victory of female candidates was influenced by the male power relation which was not absolute, the figure of female candidates and the proportional electoral system.